(3+3i)+(2+4i)=

Simple and best practice solution for (3+3i)+(2+4i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+3i)+(2+4i)= equation:


Simplifying
(3 + 3i) + (2 + 4i) = 0

Remove parenthesis around (3 + 3i)
3 + 3i + (2 + 4i) = 0

Remove parenthesis around (2 + 4i)
3 + 3i + 2 + 4i = 0

Reorder the terms:
3 + 2 + 3i + 4i = 0

Combine like terms: 3 + 2 = 5
5 + 3i + 4i = 0

Combine like terms: 3i + 4i = 7i
5 + 7i = 0

Solving
5 + 7i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 7i = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 7i = 0 + -5
7i = 0 + -5

Combine like terms: 0 + -5 = -5
7i = -5

Divide each side by '7'.
i = -0.7142857143

Simplifying
i = -0.7142857143

See similar equations:

| -7w(w-2)=5(3-w) | | 2a^2+5a+18=0 | | 4(u+1)=20 | | x+5-5x=13 | | 5x-23=5x-1 | | 2x^3+5x^2-x-6=0 | | -8x+2=-6 | | 3=x+5-4 | | y+-6x+-9=0 | | (3x^3-24)=0 | | 4(3+5w)=11 | | ln(x^2+3x+4)=0 | | -15+2(x)=-11 | | -15+2(5)= | | -2a+3-4=-1 | | -15+2(3)= | | x-3-1=2 | | 3m+2x=y | | 4 = b8 | | 4t+1=7t+10 | | 17-6x+4=3x+21-3x | | -13+12(x)=11 | | -8+14v=12v | | n+31+2n=17 | | 0=r-4+6 | | 13=u-6 | | -13+12(7)= | | 2(b+3)=14 | | 5p=-8+6p | | 18s-11s-5s=20 | | 4(7s+3)=-15 | | -194-7x=3x+66 |

Equations solver categories